Bronislawa Wajs’ Creolism and Literary Comparative Studies in Poland - Kledzik, Emilia (Porównania, 2024)
The article attempts to illustrate, using a local literary example, recent comparative theories that equate comparative studies with translation studies. Using the category of incommensurability and the figure of the Creole from Emily Apter's work as well as Edouard Glissant’s reflection on Creole languages, it analyses the original versions of the works of the Romani poet Bronislawa Wajs (Papusza). Until 2020, Wajs’ works were known to readers in a version edited by the Gypsy scholar Jerzy Ficowski. Their original form is characterised by linguistic and cultural hybridity. As in the case of the Creole languages, this feature, considered by the translator to be non-literary, was obscured in the translation. Papusza’s heteroglossia illustrates the specificity of local languages and multilingual communities, characterized by the phenomenon of continuous translation and intercultural dialogue.